Aflatoxin Contamination of Cattle’s Concentrate Feeds; A Case Study in Dar Es Salaam-tanzania - Jonathan, Sahan; Nalumansi, Irene; Birungi, Grace (Research square, 2022)
Abstract Background Aflatoxicosis associated with the consumption of aflatoxin contaminated maize and maize products has been reported in the central part of Tanzania (Chemba, Kondoa, and Kiteto), however little is known about the prevalence of aflatoxin contamination in cattle’s concentrate feed, yet maize constitutes a major component in the feed. The presence of aflatoxin in cattle’s concentrate feed lead to reduced growth rate, and milk production and results in a carryover effect on human being resulting in human health effect. This study aimed at determining the prevalence of aflatoxins contamination, the level of awareness, knowledge, and practices associated with aflatoxin contamination, and control in cattle concentrate feeds produced and sold in Dar es Salaam, Tanzania. Method Eighty- one samples of concentrate feed were collected from concentrate feed processors and sellers in four clusters Ilala, Kinondoni, Temeke, and Ubungo. The samples were nalyzed by Enzyme linked Immuno-Sorbent Assay and High-Performance Liquid Chromatography-Fluorescent Detector. The level of contamination was compared to the WHO/EAC/TBS recommended limit. Also eighty- one concentrate processors and sellers were interviewed to assess the level of awareness, knowledge, and human practices associated with aflatoxin contamination and control. Results Sixty- three 63/81 (78%) samples were contaminated with total aflatoxin (TAFs) ranging from LOD to 161.32 ppb, mean of 25.89 ± 3.3 ppb which was significantly higher than the tolerable WHO/TBS limit of 15ppb total aflatoxins (P = 0.002), Level of AFB1 in concentrate feed was ranged from LOD to 133.17 ppb, mean 18.87 ± 2.45 ppb and was significantly higher than the tolerable WHO/TBS limit 10 ppb for AFB1 (P = 0.001). The level of AFB2 was ranged from LOD to 8.21 ppb, mean 1.82 ± 0.27 ppb, AFG1 (LOD to 75.06 ppb, mean 7.75 ± 2.32 ppb) and AFG2 (LOD to 7.87 ppb, mean, 1.30 ± 0.350 ppb), among aflatoxin the level of contamination was AFB1 > AFG1 > AFB2 > AFG2, however, AFB2 and AFG2 had significant same level of contamination (p = 0.518). The samples collected from Temeke and Ilala were significant highly contaminated with aflatoxin than the WHO/TBS recommended limit (15 ppb), with TAFs of 33.63 ± 3.96 ppb, p-value = 0.00015, 30.78 ±, 7.05 ppb, pvalue = 0.034 respectively, while those from Kinondoni and Ubungo were not significantly higher than the recommended standard 15ppb (p-value, 0.71,0 .742) respectively. The level of awareness was 38% and not significant (p = 0.353) and 58/81 (72%) of respondents were not aware of the negative health effect of aflatoxins. The poor storage facility, poor handling practices, temperature, humidity and lack of awareness were the predominant factors identified to contribute a high level of aflatoxin contamination. Conclusions The results indicated that the concentrate feeds had aflatoxin concentrations which may pose risk to animals and/or human beings, economic losses due to increased cost of treatment and reduced cattle production. The use of improved pre and post-harvest management technologies, and awareness creation to animal feed value chain actors are important steps in the reduction of this problem.
Keywords: Aflatoxin; Aflatoxin contamination; Dar es Salaam; Tanzania; Concentrate feeds; Maximum Limit